“Diagnosis by Behavioral Observation” Home-Videosomnography – A Rigorous Ethnographic Approach to Sleep of Children with Neurodevelopmental Conditions - Ipsiroglu, Osman S.; Hung, Yi-Hsuan Amy; Chan, Forson; Ross, Michelle L.; Veer, Dorothee; Soo, Sonja; Ho, Gloria; Berger, Mai; McAllister, Graham; Garn, Heinrich; Kloesch, Gerhard; Barbosa, Adriano Vilela; et al. (Frontiers in Psychiatry, 2015)
Introduction Advanced video technology is available for sleep-laboratories. However, low-cost equipment for screening in the home setting has not been identified and tested, nor has a methodology for analysis of video recordings been suggested. Methods We investigated different combinations of hardware /software for home-videosomnography (HVS) and established a process for qualitative and quantitative analysis of HVS-recordings. A case vignette (HVS analysis for a 5.5-year-old girl with major insomnia and several co-morbidities) demonstrates how methodological considerations were addressed and how HVS added value to clinical assessment. Results We suggest an ‘ideal set of hardware/software’ that is reliable, affordable ( 500) and portable (= 2.8kg) to conduct non-invasive HVS, which allows time-lapse analyses. The equipment consists of a net-book, a camera with infra-red optics, and a video capture device. (1) We present an HVS-analysis protocol consisting of 3 steps of analysis at varying replay speeds: (a) basic overview and classification at 16x normal speed; (b) 2nd viewing and detailed descriptions at 4-8x normal speed, and (c) viewing, listening, and in-depth descriptions at real-time speed. (2) We also present a custom software program that facilitates video analysis and note-taking (Annotator©), and Optical Flow software that automatically quantifies movement for internal quality control of the HVS-recording. The case vignette demonstrates how the HVS-recordings revealed the dimension of insomnia caused by Restless Legs Syndrome, and illustrated the cascade of symptoms, challenging behaviors and resulting medications. Conclusion The strategy of using HVS, although requiring validation and reliability testing, opens the floor for a new ‘observational sleep medicine’, which has been useful in describing discomfort-related behavioral movement patterns in patients with communication difficulties presenting with challenging/disruptive sleep/wake behaviors.